Pengembangan Desain Pembelajaran STEM–Multirepresentasi (STEM-MR) untuk Meningkatkan Keterampilan Pemecahan Masalah Mahasiswa pada Materi Mekanika - ismet; Ketang Wiyono; Taufiq; Maghfira Aulia (Jurnal Penelitian Pendidikan IPA, 2026)
This study aims to develop a STEM–Multirepresentation (STEM-MR) learning design for Mechanics and examine its validity, practicality, and effectiveness in improving undergraduate students’ problem-solving skills. The study employed a research and development approach using the ADDIE model. The participants were 37 undergraduate students in the Physics Education Study Program at Universitas Sriwijaya. Data were collected through expert validation sheets, observation sheets, student response questionnaires, interviews, documentation, and pretest–posttest assessments. The STEM-MR design was developed as a seven-phase learning model that integrates STEM inquiry with multirepresentational scaffolding to support problem-solving in Mechanics. The results showed that the design was highly valid, with an average expert validation score of 3.87 on a 4-point scale. It was also very practical, with with a practicality score of 91%. In terms of effectiveness, students’ average scores increased from 52.25% on the pretest to 78.50% on the posttest. The normalized gain was 0.55, which falls into the medium category, and the effect size was 2.53, indicating a very large effect. These findings show that the STEM-MR learning design is valid, practical, and effective for enhancing undergraduate students’ problem-solving skills in Mechanics.